Overt Hypothyroidism and Severe Growth Retardation in a Preschool Girl with Poorly Controlled Nephrotic Syndrome: Case Report and Literature Review - Mikulevič, Joana; Tumelienė, Karolina; Kemežys, Robertas; Jankauskienė, Augustina (Acta medica Lituanica, 2023)
Background. Nephrotic children may develop thyroid hormone dysfunction due to urinary excretion of thyroid hormones. In contrast to the subclinical hypothyroidism that affects around 30% of children with nephrotic syndrome (NS), the patient in this case had overt hypothyroidism and severe growth retardation.Clinical case. A 5 years and 8 months old girl with steroid-dependent NS was referred from another center due to persistent edema and decreased diuresis, being treated with mycophenolate mofetil (MMF) 250 mg once a day and L-thyroxine 50 mcg daily since 4 months of NS onset because of hypothyroidism. Her albumin was 12.64 g/l, cholesterol 25.64 mmol/l and proteinuria 5 g/l. Severe growth retardation was observed: patient’s height was 93.5 cm (–13 cm